'Twas the night before Thanksgiving - Pilkey, Dav, 1966- (New York : Orchard Books, 1990)
School children on a field trip to Mack Nugget's farm save the lives of eight turkeys in this poem based on "The Night Before Christmas."
School Library Journal
Booklist
4.5
K-3
Keywords: Turkeys -- Fiction; Thanksgiving Day -- Fiction; Stories in rhyme; Turkeys -- Fiction; Thanksgiving Day -- Fiction; Stories in rhyme